Risk management, speculation, and derivative securities - Poitras, Geoffrey, 1954- (Amsterdam ; Boston : Academic Press, 2002)
The book presents an integrated explanation of speculative trading and risk management from the practitioner's point of view, Risk Management, Speculation, and Derivative Securities After offering a general framework for risk management and speculation using derivative securities, it explores specific applications to forward contracts and options.
Includes bibliographical references (p. 549-581) and index.
lje 21/01/14
Loans
Keywords: Derivative securities; Speculation; Risk management